The profession of methodologist: realities and prospects (Confluenţe Bibliologice, 2012)
In this study the author describes the profession of methodologist, “the most diﬃcult and at the same time the most interesting profession in library”(A. Vaneeva), outlining deﬁnitions of methodologist, related occupations, skills and knowledge, responsibilities etc… In Republic of Moldova  methodological and  specialty assistance is carried out on the basis of the Regulatory acts issued by the Ministry of Culture, the National Librarianship Council and in accordance with Regulation ”methodological assistance and specialized system in Republic of Moldova”, approved at the National Librarianship Council from the 21.12.1999. Methodological assistance and specialized system ensure national unity in Moldova, libraries aligning methodologies and librarianship modern techniques, promoted internationally. Within NLC are represented  9 national librarianship centers, 7 of which are departmental. Central Library of the State University of Republic of Moldova perform function Librarianship Departmental Center for  libraries of institutions of  higher education and secondary specialized libraries.
Keywords: methodologist; methodological assistance; specialist assistance; library management